1996
DOI: 10.1002/j.1939-4640.1996.tb01777.x
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Cell Adhesion Molecule (NCAM) Provides Clues to the Development of Testicular Leydig Cells

ARTUR MAYERHOFER,
GEORGIA LAHR,
KLAUS SEIDL
et al.

Abstract: As previously shown, Leydig cells in culture dramatically up‐regulate the expression of the neural cell adhesion molecule (NCAM) gene and express alternatively spliced forms. Because the family of NCAM adhesion molecules is known to be involved in cell migration and differentiation, we examined the potential involvement of NCAMs in Leydig cell differentiation in the developing testis. We detected NCAM‐immunoreactive cells in the rat and mouse at embryonic day (ED) 13–14 in epithelia of mesonephric tubules and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Notably, the cell cycle analysis revealed that all the Leydig cells were in G1 phase (Figure 6A), which was consistent with previous studies showing that fetal Leydig cells are mitotically inactive, [54][55][56] and that the expansion of the fetal Leydig cell population could result from transformation of progenitor cells. [57][58][59][60] Then, we analyzed the reported Leydig cell population promoting or inhibiting factor 61 expression patterns in all cell types (Figure S6B). The majority of the possible factors were expressed in the population of interstitial cells (Figure S6B,C).…”
Section: Leydig Cellmentioning
confidence: 99%
“…Notably, the cell cycle analysis revealed that all the Leydig cells were in G1 phase (Figure 6A), which was consistent with previous studies showing that fetal Leydig cells are mitotically inactive, [54][55][56] and that the expansion of the fetal Leydig cell population could result from transformation of progenitor cells. [57][58][59][60] Then, we analyzed the reported Leydig cell population promoting or inhibiting factor 61 expression patterns in all cell types (Figure S6B). The majority of the possible factors were expressed in the population of interstitial cells (Figure S6B,C).…”
Section: Leydig Cellmentioning
confidence: 99%